Identidad Cultural y Desarrollo Turístico del Cantón Tisaleo, Provincia de Tungurahua. - Llerena Ramos, Mercy Johana (2023)
“THE AIM OF THE PRESENT RESEARCH WORK IS TO ANALYZE THE INFLUENCE OF THE CULTURAL HERITAGE ON THE TOURISM DEVELOPMENT IN TISALEO CANTON, PROVINCE OF TUNGURAHUA” This document is based on the bibliographic research that addresses a conceptual analysis of topics related to the variable study , on the other hand, by the variables operationalization, the dimensions and indicators were obtained, which led the formulation of questions, to collect information from the surveys application addressed to the authorities of the Municipal Gad of the Tisaleo Canton and to the residents of the place, in order to know the degree of conformity by the use the Likert scale, as a measurement tool that helps us to tabulate and interpret the key results. The information processing, using the SPSS program, which made to generate the tables and graphs within a given period of time, the program allowed the alternative research hypothesis being accepted, which means that the customs and traditions of the canton influence to the tourist development of Tisaleo. The proposal was made based on the obtained data, with the elaboration of a travel guide leaflet, including data and information of interest of the identity customs and traditions of the Tisaleo, in order to disseminate the most representative manifestations, of the legacy that this place has, so that, it would take great interest in the community.